2008
DOI: 10.1002/dev.20330
|View full text |Cite
|
Sign up to set email alerts
|

Differential onset of infantile deprivation produces distinctive long‐term effects in adult ex‐laboratory chimpanzees (Pan troglodytes)

Abstract: Maternal or social deprivation during early infancy inevitably produces social deficiencies in juvenile chimpanzees. Hypothesizing such deficiencies to persist into adulthood (a), and, as in humans, a sensitive period in early infancy for attachment formation (b), we predicted and found behavioral differences in resocialized adult ex-laboratory chimpanzees after about 20 years of solitary confinement depending on their age at onset of deprivation: early deprived (ED; mean: 1.2 years) chimpanzees engaged signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 57 publications
5
35
0
Order By: Relevance
“…Chimpanzees that were younger when rehabilitation began reached higher levels of behavioral and social competence and spent more time in positive behaviors such as social play and affiliative behaviors and less time being inactive. These results reflect earlier findings (Kalcher et al 2008) and suggest that the development and recovery of social and behavioral deficiencies are clearly related to the age at the onset of rehabilitation.…”
Section: Influences On Recoverysupporting
confidence: 83%
See 2 more Smart Citations
“…Chimpanzees that were younger when rehabilitation began reached higher levels of behavioral and social competence and spent more time in positive behaviors such as social play and affiliative behaviors and less time being inactive. These results reflect earlier findings (Kalcher et al 2008) and suggest that the development and recovery of social and behavioral deficiencies are clearly related to the age at the onset of rehabilitation.…”
Section: Influences On Recoverysupporting
confidence: 83%
“…The goal is to promote the development of species-typical behaviors, by enhancing their welfare and social skills. Several studies have determined that chimpanzees with a previous history of maltreatment or unfavorable rearing conditions can be rehabilitated and resocialized over time (Kalcher-Sommersguter et al 2013;Kalcher et al 2008). However, most of this evidence comes from former laboratory chimpanzees (Reimers et al 2007), where chimpanzees that were caged singly at an early age (mean 1.2 yr) present higher levels of social competence than those caged singly at a later age (mean 3.6 yr) (Kalcher-Sommersguter et al 2011).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The male gibbon may have recognised the female conspecific as a more desirable social partner than humans. The gibbon never showed aversive reactions [Harlow et al, 1965;Cheyne, 2006;Clarke et al, 2006;Kalcher et al, 2008] and on the second day exhibited social patterns, and the 2 gibbons started covocalising from the fourth day. When in physical contact, normal levels of malefemale social interactions were established on the fifth day.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that early social deprivation results in decreased species-typical behaviors, impaired cognitive abilities, and increased abnormal behaviors among chimpanzees (Davenport, Rogers, & Rumbaugh, 1973;Turner, Davenport, & Rogers, 1969). Such effects may persist throughout the lives of affected individuals (Kalcher, Franz, Crailsheim, & Preuschoft, 2008;Martin, 2002). In the wild, chimpanzee infants who lost their mother demonstrated clinical symptoms of depression such as reduced physical and social activity, reduced playfulness, and increased abnormal behavior (Goodall, 1986).…”
Section: Social and Cognitive Complexity In Chimpanzeesmentioning
confidence: 99%